2016
DOI: 10.21873/anticanres.11232
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Growth and Survival Genes with Prognostic Implications in Advanced Pancreatic Cancer

Abstract: Abstract. Aim: The aim of this study was to evaluate the mRNA expression pattern of growth-and survival-related genes and assess their prognostic significance in patients withThe epidermal growth factor receptor (EGFR) pathway has a major importance in pancreatic cancer(1). Erlotinib, a tyrosine kinase inhibitor (TKI) of EGFR, was tested in combination with gemcitabine as first-line treatment in a randomized trial of patients with advanced pancreatic cancer (2). The addition of erlotinib to gemcitabine demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Notably, our study did not find significant association of RAS overexpression with RAS mutations. Similarly, a recent report also showed KRAS mutation did not correlate with mRNA expression [ 13 ]. These results suggested that RAS overexpression and mutations were independent events contributing to the pathogenesis of AML.…”
Section: Discussionmentioning
confidence: 90%
“…Notably, our study did not find significant association of RAS overexpression with RAS mutations. Similarly, a recent report also showed KRAS mutation did not correlate with mRNA expression [ 13 ]. These results suggested that RAS overexpression and mutations were independent events contributing to the pathogenesis of AML.…”
Section: Discussionmentioning
confidence: 90%
“…NFKB1 and IKBKG are part of the NF- κ B signaling pathway. As a transcription factor, NFKB1 is closely related to the risk of PDAC occurrence and prognosis [ 37 ]. Low expression of MUC4 inhibited the expression of NFKB1 , thereby downregulating the NF- κ B signaling pathway to inhibit the migration and invasion of PDAC cells along the nerve [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…AKT3 had been reported to be expressed in various cancers, including breast cancers, ovarian cancers and gliomas [21][22][23][24][25][26][27]. AKT3 mRNA expression had been reported previously in pancreatic cancer cells [28][29][30]. To our knowledge, this is the first report of AKT3 protein expression in a pancreatic cancer cell line confirmed by gene editing.…”
Section: Generation Of Kpc Cell Lines Deficient In Akt Isoforms By Cr...mentioning
confidence: 69%